(untitled) (Physical Education, Health and Social Sciences, 2025)
This systematic review investigation focuses on the association between nurse-to-patient ratios (NPRs) and patient safety-related outcomes, and the occurrence of high NPRs on factors affecting nurse well-being and nurse workforce sustainability. Although there is a vast body of evidence that supports the association between safe staffing levels and better patient outcomes and lower nurse burnout, many healthcare systems in the world are yet to realize perfect ratios. The theoretical models like Donabedian Structure-Process-Outcome (SPO) Model, Burnout Theory, and the Systems Theory will be used to examine the implications of NPRs during the review. It emphasizes the results of different case studies in different countries such as California, Queensland, and UK and proves that the results of legislated staffing ratios are better than results of non-compulsory monitoring strategies. In the paper we will also consider the problems that arise due to nurse shortages, economic pressures on nurses and the exodus of low- and middle-income country (LMIC) nurses to high-income countries. The recommendations shall be legislature, staff investment, and international collaboration to help curb these phenomena to have sustainable health care systems.